PENTINGNYA PROFESIONALITAS GURU PAUD PADA MASA PANDEMI COVID 19 - Fahmi Rieskiana (JEA (Jurnal Edukasi AUD), 2021)
AbstractThis study aims to determine the professionalism of Early Childhood teachers during the COVID-19 pandemic. The research method used is literature research method. The conclusion of this study shows that Early Childhood institutions must have adequate facilities to support learning systems during the Covid 19 period. The role of parents and the readiness of Early Childhood teachers in helping Children to learn during the Covid 19 pandemic is important factors.Keywords: Early Chilhood teachers; parents; and Covid 19